Servant Leadership Style and High-Performance Work System Practices: Pathway to a Sustainable Jordanian Airline Industry - Alafeshat, Rawan; Tanova, Cem (Mdpi, 2019)
The purpose of this study is to examine how servant leadership (SL) and high-performance work systems (HPWS) practices enable organizational performance, as shown by employee retention and employee satisfaction. Data was obtained from 300 full time employees in a private airline company in Jordan. The data was collected in three rounds, each separated by one-week time-lag. Structural equation modeling was used to test the proposed relationships and revealed that both servant leadership and HPWS practices were positively linked with employee satisfaction and retention, which were used as indicators of organizational sustainability. In order to understand how servant leadership and HPWS influence employee satisfaction and retention, we investigated the mediating role of employee engagement and discovered that it serves as a critical mechanism. The study affirmed that, in line with studies carried out in the west, servant leadership is also an effective leadership characteristic in the context of Jordan. Furthermore, the study helps to clarify the reason that servant leadership and HPWS lead to positive outcomes, due to the fact that these improve the engagement of employees. Thus, we understand that the increases in employee retention and satisfaction are due to the enhanced engagement of employees, and we show that engagement can be improved both by servant leadership and the application of HPWS in organizations. Consequently, the effectiveness and sustainability of the airline companies in Jordan will need to focus on primarily improving employee engagement.
Keywords: Servant leadership; HPWS; Employee engagement; Employee satisfaction; Employee retention; Jordanian airline industry